Statuesque : Pawel Althamer, Huma Bhabha, Aaron Curry, Thomas Houseago, Matthew Monahan, Rebecca Warren - Baume, Nicholas; Public Art Fund, New York, N.Y.; Nasher Sculpture Center, Dallas (New York : Public Art Fund, 2011)
Pawel Althamer, Huma Bhabha, Aaron Curry, Thomas Houseago, Matthew Monahan, Rebecca Warren
Published on the occasion of 'Statuesque' at City Hall Park, New York, N.Y., 02.06.2010-03.12.2010 ; Nasher Sculpture Center, Dallas, TX, 09.04.2011-21.08.2011
boek
Keywords: Figure sculpture -- 21st century -- Exhibitions; Public sculpture -- Exhibitions